x2 + 4x = x(x+4)
x2 + 4x = x(x + 4)
2x2 + (5x-4x)2 + (x-x)2 = 2x2 + x2 + 02 = 2x2 + x2 = 3x2
x(4x-2)
She isn't. 4x squared is 4 times (x squared). That is, 4 times (3 squared) = 4 times 9. If you want it to be the square of 4x (which would be the square of 4 times 3, ie, 12), you have to write it as (4x)squared.
When you multiply 4x² by 4x², you multiply the coefficients (4 * 4 = 16) and add the exponents of the variables (x² * x² = x^(2+2) = x⁴). Therefore, the result is 16x⁴.
x2 + 4x = x(x+4)
x2 + 4x = x(x + 4)
4x^2 = 2 * 2 * x * x
(4x - 7y)(4x + 7y)
2x2 + (5x-4x)2 + (x-x)2 = 2x2 + x2 + 02 = 2x2 + x2 = 3x2
x(x-4)
-6
x(4x-2)
She isn't. 4x squared is 4 times (x squared). That is, 4 times (3 squared) = 4 times 9. If you want it to be the square of 4x (which would be the square of 4 times 3, ie, 12), you have to write it as (4x)squared.
4(x^2 + x + 3)
x2 - 4x - 21 = (x-7)(x+3)